2021
DOI: 10.3390/ijerph18041968
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Season and Neighbourhood-Built Environment on Home Area Sedentary Behaviour in 9–14 Year Old Children

Abstract: There is little understanding of how the built environment shapes activity behaviours in children over different seasons. This study sought to establish how seasonal weather patterns, in a given year in a mid-western Canadian city, affect sedentary time (SED) in youth and how the relationship between season and SED are moderated by the built environment in their home neighbourhood. Families with children aged 9–14 years were recruited from the prairie city of Saskatoon, Canada. Location-specific, device-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Children aged 7-18 years with sedentary behavior for 1-2 hours and > 2 hours have 1.64 times and 1.94 times chance of being obese [35]. In Canada, children who are overweight and obese are on the rise, and they consistently do not meet the recommended guidelines for limiting sedentary (no more than 2 hours/day of screen-based activity time) [36]. Sedentary behavior has a relationship with health conditions, including mental health, obesity, type 2 diabetes mellitus, cardiovascular disease, and breast, colorectal, endometrial, and ovarian cancers [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children aged 7-18 years with sedentary behavior for 1-2 hours and > 2 hours have 1.64 times and 1.94 times chance of being obese [35]. In Canada, children who are overweight and obese are on the rise, and they consistently do not meet the recommended guidelines for limiting sedentary (no more than 2 hours/day of screen-based activity time) [36]. Sedentary behavior has a relationship with health conditions, including mental health, obesity, type 2 diabetes mellitus, cardiovascular disease, and breast, colorectal, endometrial, and ovarian cancers [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, children who are overweight and obese are on the rise, and they consistently do not meet the recommended guidelines for limiting sedentary (no more than 2 hours/day of screen-based activity time) [36]. Sedentary behavior has a relationship with health conditions, including mental health, obesity, type 2 diabetes mellitus, cardiovascular disease, and breast, colorectal, endometrial, and ovarian cancers [36]. In addition, sedentary behavior also has a negative impact on mental health, namely anxiety disorders and depression [37], [38].…”
Section: Discussionmentioning
confidence: 99%
“…A study of families with children aged 9-14 years in Saskatoon found that those living in neighbourhoods with high density of destinations and neighbourhood recreation amenities such as parks and green space were less sedentary overall and that this was more pronounced during spring and summer months. 65 A large national sample of adolescents in the United States surveyed early in the COVID-19 pandemic found that a lower proportion of racial/ethnic minority adolescents and those from lower socioeconomic status households met moderateto-vigorous physical activity guidelines during the pandemic compared to those from higher socioeconomic status households. 66…”
Section: Young Adultsmentioning
confidence: 99%
“…Children and adolescents in developed nations devote much of their discretionary time to sedentary pursuits. Sedentary behaviour (SB) is characterised by energy expenditure ≤ 1.5 metabolic equivalents ( Tremblay et al, 2017 , Bejarano et al, 2019 , Bringolf-Isler et al, 2018 , Goon et al, 2020 , Lotoski et al, 2021 ), involving predominantly prolonged sitting, watching television, reading, using the computer and other mobile devices, or passive transportation. Canadian children and youth are sedentary an average of 8.3 h per day, representing approximately 62% of their waking hours ( Larouche et al, 2016 ), with similar trends being reported in American children and adolescents ( Yang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hoffmann and colleagues reported an inverse association between household income and SB ( Hoffmann et al, 2017 ), while Atkin and colleagues observed a positive association between SES and objectively measured SB ( Atkin et al, 2013 ). At the neighbourhood level, a variety of features have been investigated, including perceived traffic-related and general area-level safety ( Bringolf-Isler et al, 2018 , Júdice et al, 2021 , Lenhart et al, 2017 , Parker et al, 2019 ), presence of green spaces and PA facilities ( Goon et al, 2020 , Parker et al, 2019 , Hinckson et al, 2017 ), and walkability, street connectivity, land use mix and density of destinations ( Hinckson et al, 2017 , Sallis et al, 2018 , Bejarano et al, 2019 , Bringolf-Isler et al, 2018 , Goon et al, 2020 , Lotoski et al, 2021 ). However, as concluded in several systematic reviews, few neighbourhood-level features are consistently associated with SB ( Stierlin et al, 2015 , Arundell et al, 2016 , Parajára et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%